Response to exposure draft on bearer plant: An insight from capture theory / Yew Kuok Weng - Yew , Kuok Weng (2020)
Despite of steady progress in global convergence of accounting standards, certain International Accounting Standards (IAS) or International Financial Reporting Standard (IFRS) remain controversial and in need of major overhaul. IAS 41, Agriculture is one of the accounting standards for specialised industry where universal acceptance has not been gained among the stakeholders across the world. Particularly, the stakeholders connected to agricultural sector often express strong criticism towards the IAS 41, but little attention has been given to them by the international accounting standard setter. The long-waited revision of IAS 41 only took place after 14 years since the issuance of IAS 41 in 2000. However, the revision only covered a very limited scope of IAS 41 whereby many of the issues as perceived by the stakeholders remained unanswered. Thus, a fuller understanding of the stakeholders’ perception on IAS 41 is considered as particularly urgent, as these insights or input eventually leads to a more robust and comprehensive accounting standard for agricultural sector. The perceived issues regarding IAS 41 is examined through analysing the comment letters in response to the exposure draft on bearer plant. By examining these comment letters thoroughly, stakeholders’ perception on the existing and proposed IAS 41 is to be documented and studied in a way to identify as to why many of the stakeholders rejected the IAS 41. Next, during the revision of IAS 41, numerous national accounting-standard regulators have been observed to promote the interest of the local agricultural firms through the IASB’s due process whereby these regulators openly support the lobbying position of their regulatees. This phenomenon is considered as unusual from the lens of normative theories of regulation, which generally assumes that regulators tend to advocate the interest of the consumers at large rather than working closely with the corporates. So far, there is insufficient empirical evidence justifying the collusion in response between the national regulators and corporates in the setting of IASB’s due process. Thus, the second objective of this study examines the interplay between them in influencing the revision of IAS 41 through the lens of regulatory capture. A direct approach of content analysis has been used to answer these research questions whereby the analysis starts with regulatory capture theory and relevant research findings as guidance for initial codes. All comment letters are coded with the respective lobbying behaviour of the stakeholders, statistically compared, and discussed in detailed. Overall, most of the respondent is favourable with the ED on bearer plant with minor interest groups opposing strongly to the proposed IAS 41 due to the limited amendments which specifically addressed the needs of certain interest groups. Further, collusion in response between the regulatees and national regulators has been revealed whereby these constituents demonstrated similar lobbying behaviour in many aspects consistently, which is an indication of regulatory capture. Content analysis further reveals that the motivation of some national regulators to take part in the IASB’s due process is to support their regulatees due to the overlapping interests among them. These findings are expected to provide valuable insights to the IASB’s annual improvement project in terms of the comprehensiveness of the IAS 41 while also contributes to the literature which relates to fair value debate and effective strategy for lobbying.